2011
DOI: 10.1007/s11595-011-0178-4
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of high surface area and well crystallized mesoporous WC at low temperature with a pore structure collapsed replication route

Abstract: An approach named "pore structure collapsed replication route" has been developed to prepare mesoporous WC materials with a high surface area (105 m 2 /g) and crystallized framework at a temperature as low as 700 ℃. The XRD, TEM, EDS, and BET characterizations were conducted to analyze the effects of the synthesis parameters and the template types on the structure of mesoporous WC. The compaction on the templates is the key to form mesoporous structure of WC while the templates help to control the size of crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Concerning about its weak resistance to moisture, EVOH has always been used to blend with hydrophobic polymer, such as low‐density polyethylene (LDPE) and polypropylene (PP). With proper processing methods, these blending systems could possess good barrier properties by laminar dispersion of EVOH . It is also reported that EVOH had a good compatibility with polyamide‐containing ionomer, which improved its flexibility and toughness .…”
Section: Introductionmentioning
confidence: 99%
“…Concerning about its weak resistance to moisture, EVOH has always been used to blend with hydrophobic polymer, such as low‐density polyethylene (LDPE) and polypropylene (PP). With proper processing methods, these blending systems could possess good barrier properties by laminar dispersion of EVOH . It is also reported that EVOH had a good compatibility with polyamide‐containing ionomer, which improved its flexibility and toughness .…”
Section: Introductionmentioning
confidence: 99%